Chronic airflow limitation in developing countries: burden and priorities - Aït-Khaled, Nadia (Dove Medical Press, 2007)
Respiratory disease has never received priority in relation to its impact on health. Estimated DALYs lost in 2002 were 12% globally (similar for industrialized and developing countries). Chronic airflow limitation (due mainly to asthma and COPD) alone affects more than 100 million persons in the world and the majority of them live in developing countries. International guidelines for management of asthma (GINA) and COPD (GOLD) have been adopted and their cost-effectiveness demonstrated in industrialized countries. As resources are scarce in developing countries, adaptation of these guidelines using only essential drugs is required. It remains for governments to set priorities. To make these choices, a set of criteria have been proposed. It is vital that the results of scientific investigations are presented in these terms to facilitate their use by decision-makers. To respond to this emerging public health problem in developing countries, WHO has developed 2 initiatives: “Practical Approach to Lung Health (PAL)” and the Global Alliance Against Chronic Respiratory Diseases (GARD)”, and the International Union Against Tuberculosis and Lung Diseases (The Union) has launched a new initiative to increase affordability of essential asthma drugs for patients in developing countries termed the “Asthma Drug Facility” (ADF), which could facilitate the care of patients living in these parts of the world.